2010
DOI: 10.1111/j.1469-8137.2010.03323.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide is involved in phosphorus deficiency‐induced cluster‐root development and citrate exudation in white lupin

Abstract: Summary• White lupin (Lupinus albus) forms specialized cluster roots characterized by exudation of organic anions under phosphorus (P) deficiency. Here, the role of nitric oxide (NO) in P deficiency-induced cluster-root formation and citrate exudation was evaluated.• White lupin plants were treated with the NO donor sodium nitroprusside (SNP) and scavenger or inhibitor of NO synthase under conditions of P deficiency (0 lM) or P sufficiency (50 lM).• Phosphorus deficiency enhanced NO production in primary and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
119
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(123 citation statements)
references
References 61 publications
(148 reference statements)
2
119
0
2
Order By: Relevance
“…Wang et al [42] showed that P deficiency induces nitric oxide production. As for auxin, the levels are highest in the pre-emergent stage, and decrease during cluster-root maturation.…”
Section: The Role Of Phytohormones and Sugars In Cluster-root Formationmentioning
confidence: 99%
“…Wang et al [42] showed that P deficiency induces nitric oxide production. As for auxin, the levels are highest in the pre-emergent stage, and decrease during cluster-root maturation.…”
Section: The Role Of Phytohormones and Sugars In Cluster-root Formationmentioning
confidence: 99%
“…In-depth study on molecular mechanisms defining the phosphate signalling pathway showed that Pup1-specific protein kinase gene, PSTOL1 is involved in regulating root growth and architecture during early stages (Gamuyao et al, 2012). Allele-specific markers for this gene have been reported recently (Pariasca-Tanaka et al, 2014).The systemic response to P starvation is carried through a complex signalling network which involves plant hormones (Nacry et al, 2005;Pérez-Torres et al, 2008;Li et al, 2012), sugars (Karthikeyan et al, 2007) and nitric oxide (Wang et al, 2010), and collectively result in the altered carbohydrate distribution between roots and shoots. Moreover, transcription factors such as PHR1 (OsPHR1, OsPHR2, PvPHR1, ZmPHR1, TaPHR1), PTF1 (OsPTF1, ZmPTF1), MYB2P-1 (OsMYB2P1), MYB62, WRKY (WRKY75, WRKY6), bHLH32 and ZAT6 are involved in the signalling network to regulate plant adaptation to P stress (Yi et al, 2005;Devaiah et al, 2007a, b;Chen et al, 2007;Valdes-Lopez et al, 2008;Zhou et al, 2008;Devaiah et al, 2009;Chen et al, 2009;Li et al, 2011;Dai et al, 2012;Wang et al, 2013).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Correa-Aragunde et al (2006) further showed that NO mediates the expression of cell cycle-regulatory genes in tomato pericycle cells to induce lateral root primordia formation, suggesting a NO-mediated auxindependent cell cycle gene regulation in tomato. Recently, NO was demonstrated to be involved in adaptive responses of white lupin to P starvation (Wang et al, 2010). Accumulation of NO was found in P-deficient white lupin roots, particularly in cluster rootlet primordia prior to and during emergence (Fig.…”
Section: Nitric Oxide Production In Cluster Rootsmentioning
confidence: 99%
“…These studies, together with the findings of Correa-Aragunde et al (2006) in tomato, support the hypothesis that NO seems to be required in lateral root initiation and root primordia formation. In addition to studies on the role of NO in cluster root formation, Wang et al (2010) also investigated the enzymes putatively involved in NO generation in cluster roots. Inhibitor studies and gene expression analyses show that a NO-synthase-like enzyme and xanthine oxidoreductase are required for the accumulation of NO in cluster roots.…”
Section: Nitric Oxide Production In Cluster Rootsmentioning
confidence: 99%